Successful Percutaneous Coronary Intervention for Atherosclerotic Coronary Lesion with Anomalous Origin of the Right Coronary Artery - Junji Matsuda; Takashi Ikenouchi; Giichi Nitta; Shunichi Kato; Kazuya Murata; Miki Kanoh; Yukihiro Inamura; Nobutaka Kato; Tomomasa Takamiya; Ken Negi; Akira Sato; Tsunehiro Yamato; et al. (Case Reports in Medicine)
Congenital coronary artery anomalies, including anomalous origin of a coronary artery, can manifest as life-threatening conditions, such as myocardial infarction or arrhythmia, and may even lead to sudden death associated with specific congenital anatomical features. Such arteries can also develop atherosclerotic lesions. This report describes the case of a 75-year-old man who was admitted to our hospital due to exertional dyspnea. The right coronary artery was found to originate from the left coronary sinus and exhibit tight stenosis due to atherosclerosis, causing effort angina pectoris. This case highlights the fact that coronary artery anomalies can cause angina pectoris via both atherosclerotic and nonatherosclerotic effects, and successful revascularization was achieved noninvasively via percutaneous coronary angioplasty.